Trajetórias dos filhos da luta pela terra: o assentamento "Che" em Itaberaí - Goiás - Santos, Nilda Ferreira dos (2022)
By approaching the movement of struggle for land, this thesis seeks to analyze the dynamic reality of a rural settlement in the city of Itaberaí, in the Brazilian state of Goiás. The research seeks to understand how a second generation of people from the “Che” Settlement led their lives over ten years of its consolidation, based on the struggle for land. We also seek to understand the extent to which these new generation are willing to assume a way of life in the countryside, continuing the work started by their parents, in view of the difficulties particularly imposed on a settlement. In this way, we highlight how the technological development that has been incorporated into the mode of production in rural areas, as well as the culture of agribusiness, which aims at large-scale production for exportation, are far from the reality of the small producers, even more specifically in the case of settlers. To account for this dynamic reality, methodologically, the research is based on historical-dialectical materialism, in a neo-Marxist perspective proposed by Henri Lefebvre, whose regressiveprogressive methodological procedure also guides the research, aiming at the articulation between Sociology and History, together with the contributions of José de Souza Martins on this object that, although it is inserted in the rural environment, has peculiar characteristics that make it different.